Caring for the premature baby - an individual case study - Nowak, Agnieszka; Raczek, Natalia; Bogacki, Michał; Krawczyk, Bożena (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Premature baby is called this way because of its early birth — between 22nd and 37th week of pregnancy — and it is characterized by immaturity of the nervous and respiratory systems. Premature births are worldwide cause of perinatal morbidity and mortality among newborns. The most common complications of prematurity is infant respiratory distress syndrome, periventricular leukomalacia, bronchopulmonary dysplasia, necrotizing enterocolitis, retinopathy of prematurity and hypoxia. Extremely immature preterm newborns require comprehensive medical and nursing care in order to grow up properly. Aim. Aim of the study was analysis of the problem of prematurity based on an individual case study. Material and methods. Analysis of selected patients’ medical records from Neonatal Pathology Department of the Szpital Wojewódzki in Bielsko-Biała. Results and conclusions. Many times severe clinical condition of preterm infants is associated not only with the usual complications of prematurity, but also the accompanying malformations. In our case, clinically important was congenital malformation of lungs, which launched series of advanced problems. Therefore, even more increased childcare was needed. However, the described case indicates that comprehensive medical therapy, nursing and rehabilitation increase the chances of survival, proper development and the return to health of premature babies, even those born with severe clinical condition.